Studies Theoretical the Contribution of Feminism Philosophy Towards Women's Involvement in the Contemporary World of Work - Jumriani Jumriani; Bambang Subiyakto; Rusmaniah Rusmaniah; Syarifuddin Syarifuddin (Program Studi Pendidikan IPS, 2025)
This theoretical study examines the contribution of feminist thought to women's involvement in the contemporary workplace, with a particular focus on the interconnections between various feminist theories and their practical implications in the Indonesian context. Through a comprehensive literature analysis and examination of empirical data, this study reveals a complex web of perspectives and theoretical Feminism that has shaped women's participation in the modern workplace. This study demonstrates that integrating various streams of Feminism, from liberal Feminism to Islamic Feminism, has created a more nuanced understanding of gender equality in the workplace. This study identifies how the foundations of theoretical knowledge have influenced the development of organizational policies and practices in Indonesia, demonstrating that successful implementation of gender equality initiatives requires a contextual approach that considers the intersections of gender with class, religion, and local culture. Data analysis from across sectors shows significant progress in women's labor force participation, with organizations adopting an integrated feminist approach experiencing increased productivity. However, the study also reveals ongoing challenges in implementing the theoretical framework in the unique socio-cultural context of Indonesia. This study concludes that the contribution of feminist thought to women's involvement in the workplace is multidimensional and interconnected. This study emphasizes the importance of developing implementation mechanisms that consider local complexities while maintaining universal principles of gender equality. The study recommends strengthening policy implementation mechanisms, developing holistic empowerment programs, and establishing collaborative platforms between academics, practitioners, and policymakers to facilitate ongoing dialogue on implementing feminist theory in contemporary work.